Encyclopedia of Life Sciences 2017
DOI: 10.1002/9780470015902.a0027093
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid System: An Update

Abstract: The endocannabinoid system (ECS) is nowadays considered as an important neurotransmitter system and, although the chemistry, biochemistry and pharmacology of endocannabinoids (eCBs) have been widely investigated, quite some pieces are still missing to fully understand how this system works. The discovery of anandamide (AEA) and 2‐arachidonoylglycerol (2‐AG) dates back to the beginning of 1990 and, since then, their molecular targets, biosynthetic and catabolic enzymes have been identified. In addition, selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
2
0
2
Order By: Relevance
“…It has been verified that 2-AG could modulate synaptic function, produce neuroprotection, and stimulate MAPK family by bonding to and activating two receptors, CB 1 R and CB 2 R, which are two G-protein-coupled receptors and have been grossly identified in astrocytes [ 23 ]. Previous studies have shown that activation of CB 1 R or CB 2 R results in anti-inflammation, prevention of neurodegeneration, and inhibition of nociceptive signaling pathways [ 24 26 ], as well as stimulation of the MAPK cascade [ 27 29 ]. Interestingly, activation of CB 1 R or CB 2 R also could inhibit stress-induced activation of the MAPK cascade.…”
Section: Introductionmentioning
confidence: 99%
“…It has been verified that 2-AG could modulate synaptic function, produce neuroprotection, and stimulate MAPK family by bonding to and activating two receptors, CB 1 R and CB 2 R, which are two G-protein-coupled receptors and have been grossly identified in astrocytes [ 23 ]. Previous studies have shown that activation of CB 1 R or CB 2 R results in anti-inflammation, prevention of neurodegeneration, and inhibition of nociceptive signaling pathways [ 24 26 ], as well as stimulation of the MAPK cascade [ 27 29 ]. Interestingly, activation of CB 1 R or CB 2 R also could inhibit stress-induced activation of the MAPK cascade.…”
Section: Introductionmentioning
confidence: 99%
“…The endocannabinoid system is a lipid signaling system that is involved in a wide range of physiological and pathological processes such as energy metabolism and inflammation. Three major components constitute the endocannabinoid system: endocannabinoids, cannabinoid receptors, and endocannabinoid metabolism (Battista et al 2006). Endocannabinoids are endogenously-produced bioactive lipids that activate cannabinoid receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente, receptores CB1 são ativados por ligantes endógenos derivados de lipídeos de membrana chamados de endocanabinóides (Battista et al, 2006;Boyd, 2006;Di Marzo, Petrosino, 2007). Inúmeros trabalhos têm proposto um papel importante para o sistema endocanabinóide em diferentes condições fisiológicas e fisiopatológicas, dentre elas estão Doença de Parkinson, Alzheimer, depressão, inflamação, obesidade e dor neuropática (Battista et al, 2006;Boyd, 2006;Di Marzo, Petrosino, 2007 (Gilron, Coderre, 2007;Iversen, Chapman, 2002;Pertwee, 2001;Walker, Huang, 2002).…”
Section: Sistema Canabinóide E Seu Envolvimento Na Nocicepçãounclassified
“…Inúmeros trabalhos têm proposto um papel importante para o sistema endocanabinóide em diferentes condições fisiológicas e fisiopatológicas, dentre elas estão Doença de Parkinson, Alzheimer, depressão, inflamação, obesidade e dor neuropática (Battista et al, 2006;Boyd, 2006;Di Marzo, Petrosino, 2007 (Gilron, Coderre, 2007;Iversen, Chapman, 2002;Pertwee, 2001;Walker, Huang, 2002). Na nocicepção, foi demonstrado que o Sistema Endocanabinóide atua na regulação da via descendente de dor, em diferentes níveis da via nociceptiva, modulando a inibição da AC, a ativação de canais de potássio e a inibição dos canais de cálcio, exercendo efeito inibitório sobre a liberação de transmissores, agindo de maneira distinta, mas paralela àquela que envolve os opióides (Iversen, Chapman, 2002;Rang et al, 2007).…”
Section: Sistema Canabinóide E Seu Envolvimento Na Nocicepçãounclassified